[PP.23.07] ACUTE SILDENAFIL USE LOWER 24H BLOOD PRESSURE LEVELS IN RESISTANT HYPERTENSION A RANDOMIZED, PLACEBO CONTROLLED, CROSS-OVER TRIAL. (September 2016) - Catharina, A. Santa; Modolo, R.; Ritter, A.; Sabbatini, A.; Brunelli, V.; Correa, N.; Quinaglia, T.; Moreno, H.; De Faria, A.
Abstract : Objective: The present study sought to evaluate whether acute administration of sildenafil compared with placebo improves ambulatory BP levels in RHTN subjects. Design and method: This interventional, single-blinded, placebo-controlled, one-way crossover trial included 26 patients with true RHTN. Increasing oral doses of sildenafil were given at 30 minute-interval (37.5 mg, 50 mg and 100 mg) in a single day. After a washout period of 14 days, patients received consecutive oral doses of placebo and the protocol was repeated. Before and after each protocol day (sildenafil and placebo), patients underwent 24-hour ABPM evaluation. Results: The reduction of systolic (−8.8 ± 1.4 vs. 1.3 ± 1.2mmHg), diastolic (−5.3 ± 3.3 vs. 1.8 ± 1.1mmHg) and mean (−7.9 ± 3.6 vs. 0.8 ± 0.9mmHg) 24-hour BP were higher after sildenafil compared with placebo. The main differences were observed on daytime BP levels (systolic; −6 ± 4.7 vs. 4.4 ± 1.5 mmHg; and mean: −4.8 ± 3.9 vs. 3.5 ± 1.4 mmHg; sildenafil vs. placebo, respectively). Conclusions: Our study suggests that an acute high-dose load of sildenafil improves ABPM parameters in resistant hypertensive patients. Considering its antihypertensive effect, sildenafil may represent a therapeutic option for the treatment of RHTN.